Low-temperature hydrolysis of carbonyl sulfide in blast furnace gas using Al2O3-based catalysts with high oxidation resistance. (15th February 2022) - Cao, Rui; Ning, Ping; Wang, Xueqian; Wang, Langlang; Ma, Yixing; Xie, Yibing; Zhang, Hui; Qu, Jiaxin
Highlights: Low-temperature hydrolysis of carbonyl sulfur in complex gas fractions of blast furnace gas. Needle-like are obtained due toMoO3 nanoparticle insert in the of potassium oxide deposited on alumina Nano sheet structures, enhance the catalytic properties of the prepared composites. The Mo atoms transfer electrons and excite the adsorbed H2O to produce –OH, while enhancing the basic sites that can stabilize the hydrolysis of COS. The synergistic effect of Mo species and K2O over Al2O3 promoted the removal of COS and inhibited the production of sulfate. The introduction of Mo and K increases the number of weakly basic sites in the catalyst while decreasing the amount of lattice oxygen in the catalyst, and the NH3 adsorption IR shows a decrease in acidic sites. COS is first adsorbed on the catalyst surface, bicarbonate and thiocarbonate are the main intermediates of the catalyst, and H2O is involved in the reaction by reacting with transition species to eventually generate sulfate to deactivate the catalyst. Abstract: Water vapor, O2 and various sulfides in blast furnace gases affect the carbonyl sulfide (COS) hydrolysis reaction. In this study, we investigated the hydrolysis and deactivation mechanisms of a series of catalysts that were synthesized by depositing K2 O and MoO3 on industrial alumina-based catalysts. Alumina nanosheets were deposited with potassium oxide, in which MoO3 nanoparticles were incorporated resulting in needle-like structures. The modified catalysts had substantially enhanced COS hydrolysis activity at low temperatures. The introduction of K2 O and MoO3 significantly increased the number of weakly basic sites on the catalysts and reduced the lattice oxygen content. The catalysts exhibited high oxidation resistance and hydrolysis properties. According to the poisoning mechanism, the deposition of sulfate species tended to reduce weakly basic sites. High-valent Mo easily excited the adsorbed H2 O on the catalysts, producing –OH groups that facilitated the COS hydrolysis reaction. This modification facilitates the further investigation of catalysts capable of promoting COS hydrolysis and their application in the manufacturing industry.